The Natural Product Elegaphenone Potentiates Antibiotic Effects against Pseudomonas aeruginosa. Issue 25 (16th May 2019) - Zhao, Weining; Cross, Ashley R.; Crowe‐McAuliffe, Caillan; Weigert‐Munoz, Angela; Csatary, Erika E.; Solinski, Amy E.; Krysiak, Joanna; Goldberg, Joanna B.; Wilson, Daniel N.; Medina, Eva; Wuest, William M.; Sieber, Stephan A.
Abstract: Natural products represent a rich source of antibiotics that address versatile cellular targets. The deconvolution of their targets via chemical proteomics is often challenged by the introduction of large photocrosslinkers. Here we applied elegaphenone, a largely uncharacterized natural product antibiotic bearing a native benzophenone core scaffold, for affinity‐based protein profiling (AfBPP) in Gram‐positive and Gram‐negative bacteria. This study utilizes the alkynylated natural product scaffold as a probe to uncover intriguing biological interactions with the transcriptional regulator AlgP. Furthermore, proteome profiling of a Pseudomonas aeruginosa AlgP transposon mutant provided unique insights into the mode of action. Elegaphenone enhanced the elimination of intracellular P. aeruginosa in macrophages exposed to sub‐inhibitory concentrations of the fluoroquinolone antibiotic norfloxacin. Abstract : Antibiotics testing : The natural product elegaphenone kills Gram‐positive Enterococcus faecalis and inhibits the virulence of Gram‐negative Pseudomonas aeruginosa . Its intrinsic benzophenone structure was utilized to determine its cellular targets by chemical proteomics.